Фонологическая интерпретация нейтрального гласного и r в английском языке - Клейнер, Ю. (Kalbotyra, 1977)
The paper is concerned with the discussion of the phonemic status of the SBE [ə] and [r], previously dealt with by N. S. Trubetzkoy in his “Grundzüge der Phonologie”. The distribution of [r] reveals the identity of the positions where it occurs (syllable initial, intervocalic, or hiatus), as well as the identity of r’s in these positions. The author comes to the conclusion that, when pre-consonantal or before the pause, the allophone of word final r is not phonetic zero, but rather an unstable [ə] which is therefore an allophone of the same phoneme as [r]. In this study such allophones are termed prosodic since the contrast between them is handled by means of a feature belonging to the syllable level (in this case it is syllabicity of the vocalic [ə] vs non-syllabicity of the consonantal [r]). In addition, it is maintained that [ə] and [ə:] both have [ə]-glides and thus are centring diphthongs belonging to the same phoneme.